2021
DOI: 10.2495/ei-v4-n4-323-339
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Ecosystem Analysis of Urban Ponds: Implications for Synergistic Benefits and Potential Trade-Offs Resulting from Retrofitting of Green Roofs in Their Catchments

Abstract: This paper provides a summary of ecological functioning, biodiversity and water chemistry of two sustainable drainage systems (SuDS) ponds, and compares the level of ecosystem services with those attainable by retrofitting green roofs (GRs) in the ponds' catchments. These study sites are characterised by relatively high diversity of habitats, including aquatic, mesic and terrestrial; the importance of the latter is highlighted using the analysis of vascular plants and calcicolous lichens. Both SuDS sites provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…However, based on the demonstrated studies, GRs have a strong role in stormwater runoff management [67], as shown in our results. It should also be noted that the alleviation of runoff may result in a decrease in water quality downstream-another issue that should be investigated by further research [100].…”
Section: Rainwater Runoffmentioning
confidence: 99%
See 1 more Smart Citation
“…However, based on the demonstrated studies, GRs have a strong role in stormwater runoff management [67], as shown in our results. It should also be noted that the alleviation of runoff may result in a decrease in water quality downstream-another issue that should be investigated by further research [100].…”
Section: Rainwater Runoffmentioning
confidence: 99%
“…Therefore, official guidance and tests should be followed during the construction of GRs and should not necessarily be used as a primary tool for water quality improvement. However, it was proven that pollution would be lower from GRs compared to conventional roofs in every case [108,110], although recent work suggests that the deterioration of water quality in receiving water bodies may result from complex interactions between runoff quantity and chemistry [100]. Further studies are needed to investigate these issues.…”
Section: Runoff Water Qualitymentioning
confidence: 99%